The role of optical coherence tomography in the evaluation of para-chiasmal lesions: a systematic review and meta-analysis - Lim, Khai Shin Alva; Tng, Wen Xu Abel; Theng, Wei De Bryan; Lee, Bernett Teck Kwong; Chin, Chee Fang; Li, Kelvin Zhenghao; Moss, Heather E. (Frontiers in Ophthalmology, 2026)
IntroductionWhile magnetic resonance imaging is currently the primary diagnostic tool for pituitary tumors, optical coherence tomography (OCT) may be used in evaluating the visual pathway impact of these lesions. This study evaluates the utility of OCT in patients with chiasmal compression from para-chiasmal lesions and determines its role in predicting visual field outcomes post-operatively.MethodsA search of five databases identified OCT studies in patients with neoplasms affecting the optic chiasm. Meta-analyses compared i) healthy controls versus patients, ii) good versus poor visual recovery post-operatively, and iii) patients with visual field defects (VFDs) versus those without. Standardized mean differences (SMDs) and mean differences (MDs) were used.ResultsA review of 97 studies (5,300 patient eyes and 2,209 controls) demonstrated significantly thinner peripapillary retinal nerve fiber layer (pRNFL), macular RNFL (mRNFL), macular ganglion cell complex (mGCC), and macular ganglion cell–inner plexiform layer (mGCIPL) in patients as compared to controls. On pRNFL analysis, four-sector analysis demonstrated that patients had thinner RNFL in all quadrants compared to controls, with the greatest thinning in the inferior quadrant (MD −16.37 μm [−22.35, −10.39]) and the least in the nasal quadrant (MD −10.91 μm [−16.45, −5.38]). mRNFL analysis showed the greatest thinning in the supero-nasal (MD −11.57 μm [−19.32, −3.83]) and infero-nasal sectors (MD −11.39 μm [−17.38, −5.40]). The meta-analysis of mGCIPL sectors found the infero-nasal region to have the most thinning. Patients with good visual recovery had higher pre-operative mean pRNFL thickness (MD 11.35 μm [6.20, 16.49]).DiscussionAssociations between OCT changes, neoplasms affecting the optic chiasm, and visual outcomes demonstrate its potential to support diagnosis and prognosis for patients with para-chiasmal lesions. Further research is needed to ascertain the relevance of pre-perimetric OCT changes.